Determinants of culinary MSME sustainability: the role of adaptation strategy in Bangka Belitung - Rani Rani; Suhardi Suhardi; Nadia Sri Rejeki (Economic: Journal Economic and Business, 2026)
This study aims to analyze the influence of access to financing, consumer trust, and business networks on the sustainability of culinary MSMEs, with adaptation strategies as a mediating variable in the post-pandemic period. This study used a quantitative approach with the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method. Data were collected from culinary MSMEs in Bangka Belitung through a purposive sampling technique. The results showed that access to financing, consumer trust, and business networks significantly influenced adaptation strategies. Furthermore, adaptation strategies were shown to have the strongest and most significant influence on business sustainability and acted as a mediator in the relationship between the independent variables and business sustainability. Meanwhile, access to financing did not have a direct effect on business sustainability. These findings indicate that the sustainability of culinary MSMEs is determined not only by the availability of resources but also by the ability of business actors to adapt business strategies to environmental changes. Therefore, strengthening adaptive capacity is a key factor in increasing the resilience and sustainability of culinary MSMEs.